2016
DOI: 10.1016/j.polymer.2016.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of block sequence and molecular weight on morphological, rheological and dielectric properties of weakly and strongly segregated styrene-isoprene triblock copolymers

Abstract: In this work, morphological, thermal, viscoelastic and dielectric properties of triblock copolymers consisting of styrene (S) and isoprene (I) blocks are discussed. SIS and ISI triblock copolymers were synthesized by sequential anionic polymerization, three of them exhibiting molecular weights below the entanglement molecular weight M e , three of them exhibiting molecular weights in the order of M e and two of them exhibiting molecular weights above M e . The objective of this work is the investigation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 68 publications
2
23
0
2
Order By: Relevance
“…The observed results correspond to the calculated entanglement molecular weight M e , which showed a decrease after modification (see Table 1 ). The M e of unfunctionalized I 5 S 90 I 5 62 is 21.1 kg/mol, which is in good agreement with the literature [ 41 ]. For comparison, the M e of PS is about 17 kg/mol, and that of pure PI is about 6 kg/mol [ 44 ].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…The observed results correspond to the calculated entanglement molecular weight M e , which showed a decrease after modification (see Table 1 ). The M e of unfunctionalized I 5 S 90 I 5 62 is 21.1 kg/mol, which is in good agreement with the literature [ 41 ]. For comparison, the M e of PS is about 17 kg/mol, and that of pure PI is about 6 kg/mol [ 44 ].…”
Section: Resultssupporting
confidence: 90%
“…For microphase-separated polymers, G ′ shows at low frequencies a plateau arising from the increased elasticity, with PI acting as a softener (with T g,PI << T g,PS ). For I 10 S 83 I 7 67 , which was investigated by Georgopanos et al [ 41 ]—with similar composition compared to the presented block copolymers of this work, but with different microstructures of PI—the terminal flow regime is clearly visible at a temperature of 180 °C, indicating a disordered state (at room temperature, microphase separation was observed with small angle X-ray scattering). Shabbir et al [ 52 ] observed for poly( n -butyl methacrylate) similar deviations with slopes of 1 and 0.5 for G ′ and G ′′, respectively, which were explained by the presence of hydrogen bonds.…”
Section: Resultsmentioning
confidence: 51%
See 2 more Smart Citations
“…Ähnliche Effekte wurden für Poly(styrol‐ b ‐isopren‐ b ‐styrol) beobachtet: bei niedrigem M n wurde eine Glasübergangstemperatur beobachtet ( M n =11 000 g mol −1 , T g =38 °C), bei höheren M n ‐Werten traten zwei dazwischenliegende Glasübergangstemperaturen auf ( M n =16 000 g mol −1 , T g,1 =−48 °C, T g,2 =43 °C) und bei großem M n wurden zwei Glasübergangstemperaturen, ähnlich zu den Homopolymeren, detektiert ( M n =161 000 g mol −1 , T g,1 =−65 °C, T g,2 =105 °C) …”
Section: Methodsunclassified